ةيبرعلا ةقطنملل ةيجراخلا ةراجتلا ةرشن, نورشعلاو عباسلا ددعلا - United Nations (United Nations, 2019)
This Bulletin presents data and statistical indicators on external and intraregional trade in goods in ESCWA member countries. Data are presented in time series until 2017 and were drawn primarily from national sources, and from secondary sources when needed. The Bulletin aims to assist policymakers, analysts, researchers and other users at the national, regional and international levels. The Bulletin comprises three parts. Part I is on external trade and contains tables on annual trade growth rates in the region, the total values of imports and exports and the percentage of those values by section of the Harmonized Commodity Description and coding System (HS). Part II is on the directions of trade and contains tables on the imports and exports of each member country with major countries and economic groupings in the world in addition to country profiles that summarizs external trade and selected trade indicators. Part III is on intraregional trade and contains tables on intraregional imports and exports as a share of total imports and exports by country and HS section.